Supporting model data for study detailing the implementation of ice nucleating particle functionality in Unified Model - Varma, Vidya (5336818) (2021)
In our recent study using the Unified Model, we have introduced a simple Ice Nucleating Particles functionality into the Unified Model to study its impact on the Southern Ocean short-wave radiation biases. By using mineral dust as an indicator for ice nucleating particles in the model, this parametrisation thus captures the impact of ice nucleating particles on the cloud distribution due to its general paucity over the Southern Ocean region. We implemented a prognostic parametrisation whereby the heterogeneous ice nucleation temperature is made to vary three-dimensionally as a function of the mineral dust distribution in the model. As a result, those regions with less dust number density would have lower nucleation temperature compared to the default global value in the model of −10C. This approach improves the physics of the model with minimal complexity. The data set included here cover all the model data used in this study/publication.